Computational study of highly efficient SnO2 ETL-based inorganic perovskite solar cell - Arith, Faiz; Mohd Rahim, Farah Liyana; Muhammad Fauzi Peong, Nurin Izzati; Ahmad Jalaludin, Nabilah; Salehuddin, Fauziyah; Muhammad Mustafa, Ahmad Nizamuddin; Mohd Shah, Ahmad Shahiman (Wydawnictwo SIGMA-NOT, 2024)
The growing demand for high Power Conversion Efficiency (PCE) in Perovskite Solar Cells (PSCs) has increased the need for the introduction of new material combinations. The conventional TiO2 Electron Transport Layer (ETL) has reached its maturity limit, and no further progress can be made. Therefore, the replacement with the SnO2 layer is seen as very reasonable. Furthermore, the crystallization of TiO2 requires a high-temperature annealing process, thus obliterating its use in flexible applications, and increasing fabrication costs. This study numerically elaborated on the potential of SnO2 as an ETL in PSCs using the Solar Cell Capacitance Simulator (SCAPS-1D). The combination of SnO2 ETL with solid-state CUSCN HTL is also deliberated to provide an alternative to the use of all inorganic PSCs, where the cell consists of ITO/ SnO2 /CH3NH3PbI3/CuSCN/Au. Numerous key parameters of SnO2 have influenced cell performance, including operating temperature, layer thickness, dopant density and defect density state. The highest PCE has been recorded reaching up to 24.14% with FF of 85.99%, VOC of 1.15V, and JSC of 24.42 mA/ cm2 from the optimized cell structure. However, it can be seen that the impact of high defect density has had a profound effect on PCE performance, thus illuminating the comprehensive concern required in containment. This may provide a guideline prior to the future fabrication of PSCs utilizing the SnO2 as ETL.